The Effect of Trust and Satisfaction on Outpatient Patient Loyalty at Hospital X - I Gusti Ayu Tania Dwi Cahyanti (Green Publisher Indonesia, 2024)
This study aims to examine the impact of patient trust and satisfaction on patient loyalty at Hospital X in Semarang. The research employs a quantitative method with a cross-sectional approach, where data were collected through questionnaires distributed to outpatient medical patients. The results show that both patient trust and satisfaction play significant roles in shaping patient loyalty at the hospital. Patient who are satisfied with the services provided and have a high level of trust in the medical staff tend to exhibit stronger loyalty. These findings highlight the importance of managing patient trust and satisfaction as key factors in building patient loyalty within the hospital. In conclusion, improving quality of service that enhances patient trust and satisfaction will directly contribute to increased patient loyalty to the hospital.